2012
DOI: 10.1103/physrevb.86.115206
|View full text |Cite
|
Sign up to set email alerts
|

Rabi oscillation and electron-spin-echo envelope modulation of the photoexcited triplet spin system in silicon

Abstract: We report on a pulsed electron paramagnetic resonance (EPR) study of the photoexcited triplet state (S = 1) of oxygen-vacancy centers in silicon. Rabi oscillations between the triplet sublevels are observed using coherent manipulation with a resonant microwave pulse. The Hahn echo and stimulated echo decay profiles are superimposed with strong modulations known as electron-spin-echo envelope modulation (ESEEM). The ESEEM spectra reveal a weak but anisotropic hyperfine coupling between the triplet electron spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…12 The SL1 center has been extensively studied by continuous-wave (cw) and pulsed electron paramagnetic resonance (EPR) methods. 13,14 Read-out of the SL1 spin state is also possible by electric means using a spindependent recombination process involving the SL1 center. Two experimental techniques are used for this, spin-dependent conductivity (SDC), 15 where the conductivity changes are monitored via microwave (mw) reflectivity, and electrically detected magnetic resonance (EDMR), 15,16 where the conductance is measured via a dc current flowing through the sample.…”
Section: Introductionmentioning
confidence: 99%
“…12 The SL1 center has been extensively studied by continuous-wave (cw) and pulsed electron paramagnetic resonance (EPR) methods. 13,14 Read-out of the SL1 spin state is also possible by electric means using a spindependent recombination process involving the SL1 center. Two experimental techniques are used for this, spin-dependent conductivity (SDC), 15 where the conductivity changes are monitored via microwave (mw) reflectivity, and electrically detected magnetic resonance (EDMR), 15,16 where the conductance is measured via a dc current flowing through the sample.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this condition, the group led by Keio University employed vacancy-oxygen complexes in silicon that had 29 Si nearest neighbors. [82][83][84] This defect is unique as it can be excited into the spin triplet state to achieve large electron spin polarization that can be transferred to the nearby 29 Si nuclear spins. This allowed a very large, most likely >90%, polarization of the 29 Si nuclear spins.…”
Section: ] 28mentioning
confidence: 99%
“…The experiments were performed with nand p-type Czochralski-grown silicon crystals containing 0.59, 4.7, and 99.2% of 29 Si isotope. Si samples doped with phosphorus (N (P) ≈ 10 15 cm −3 ) and containing 0.59 and 99.2% of the 29 Si isotopes were irradiated at room temperature by γ -rays from the 60 Co source with the dose of 8 × 10 18 γ /cm 2 . In addition, two samples of n-Si (N (P) ≈ 5 × 10 16 cm −3 ) and highresistance (∼1000 •cm) p-type Si with the natural (4.7%) abundance of the 29 Si isotopes were irradiated by 1-MeV electrons with the dose of 10 18 e/cm 2 at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…58 A recent transient experiment with pulsed light has shown that A-centers are transformed to SL1 immediately after the light illumination followed by two electron spins bound to each SL1, reaching almost 100% polarization between magnetic sublevels with the timescale of 0.1 ms in the favorable temperature and external magnetic field condition, and such highly polarized triplets decay to singlet ground states with the timescale of a few milliseconds. 60 Under the continuous illumination employed in the present study, such photoexcitation and decay cycles are expected to occur continuously, and a certain steady-state condition is established among the ensemble of O-V centers, leading to large DNP of the surrounding 29 Si nuclear spins.…”
Section: Introductionmentioning
confidence: 93%